Shadow Cast of the Schwarzschild-like Black Holes - Babayeva, Flora (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The Event Horizon Telescope has recently seen the edge of a black hole. This fruitful outcome reveals a fine structure near the black hole horizon. The photon ring and shadow have been clearly observed which provides us with a good opportunity to test general relativity in the regime of strong gravity. In this thesis first we study Schwarzschild black hole and its properties, then we calculate null geodesics of Schwarzschild metric from Euler-Lagrange to find its shadow cast which is two dimensional dark zone in the celestial sphere caused by the strong gravity of the black hole. Last, we study the shadow of the quantum corrected Schwarzschild black hole. Hence, we discuss the effect of the quantum on the shadow of the black hole. Keywords: Gravitation, Black holes, Shadow, Null geodesics, Quantum Corrected Black Holes.

ÖZ: Event Horizon Teleskobu yakın zamanda bir kara deliğin resmini gözlemledi. Bu önemli sonuç, kara delik ufkunun yakınında ince bir yapı ortaya koyuyor. Foton halkası ve gölge açıkça gözlemlendi, bu da bize kuvvetli yerçekimi rejiminde genel göreliliği test etmek için iyi bir fırsat sağladı. Bu tezde önce Schwarzschild kara deliği ve özelliklerini inceliyoruz, ardından kara deliğin güçlü yerçekiminin neden olduğu göksel küredeki iki boyutlu karanlık bölge olan gölge dökümünü bulmak için Euler Lagrange'dan Schwarzschild metriğinin sıfır jeodeziklerini hesaplıyoruz. Son olarak, kuantum düzeltmeli Schwarzschild kara deliğinin gölgesini inceliyoruz. Bu nedenle kuantumun kara deliğin gölgesi üzerindeki etkisini tartışıyoruz. Anahtar Kelimeler: Yerçekimi, Kara delikler, Gölge, Sıfır jeodezikleri, Kuantum Düzeltilmiş Kara Delikler.
Master of Science in Physics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2021. Supervisor: Assoc. Prof. Dr. Ali Övgün.
Keywords: Physics; Black Holes--Physics; Gravitation; Black holes; Shadow; Null geodesics; Quantum Corrected Black Holes